2001
DOI: 10.1016/s1097-2765(01)00291-x
|View full text |Cite
|
Sign up to set email alerts
|

Net1 Stimulates RNA Polymerase I Transcription and Regulates Nucleolar Structure Independently of Controlling Mitotic Exit

Abstract: The budding yeast RENT complex, consisting of at least three proteins (Net1, Cdc14, Sir2), is anchored to the nucleolus by Net1. RENT controls mitotic exit, nucleolar silencing, and nucleolar localization of Nop1. Here, we report two new functions of Net1. First, Net1 directly binds Pol I and stimulates rRNA synthesis both in vitro and in vivo. Second, Net1 modulates nucleolar structure by regulating rDNA morphology and proper localization of multiple nucleolar antigens, including Pol I. Importantly, we show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
98
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(108 citation statements)
references
References 34 publications
10
98
0
Order By: Relevance
“…In other mutants, such as those of the Set1p methyltransferase or the Swi/Snf remodeling complex, silencing defects and effects on chromatin modification are pronounced, yet no defects have been reported for Pol I transcription and rDNA recombination may be either unaffected or suppressed (Bryk et al, 2002;Dror and Winston, 2004). By comparison, Net1p directly binds Pol I and has the capacity to promote transcription (Shou et al, 2001), with no apparent effects on recombination. Intriguingly, transcription within the rDNA by Pol I itself is required for silencing and for the spread of silencing toward the centromere (Buck et al, 2002).…”
Section: Esa1p Is a Distinct Rdna Silencing Protein Important For Nucmentioning
confidence: 99%
“…In other mutants, such as those of the Set1p methyltransferase or the Swi/Snf remodeling complex, silencing defects and effects on chromatin modification are pronounced, yet no defects have been reported for Pol I transcription and rDNA recombination may be either unaffected or suppressed (Bryk et al, 2002;Dror and Winston, 2004). By comparison, Net1p directly binds Pol I and has the capacity to promote transcription (Shou et al, 2001), with no apparent effects on recombination. Intriguingly, transcription within the rDNA by Pol I itself is required for silencing and for the spread of silencing toward the centromere (Buck et al, 2002).…”
Section: Esa1p Is a Distinct Rdna Silencing Protein Important For Nucmentioning
confidence: 99%
“…Our previous work showed that the TAB6-1 allele, which codes for a dominant "hyperactive" form of Cdc14p, 31 suppressed the daughterly phenotype of FEAR pathway mutants. 15 Although Ase1p is not upstream of the FEAR pathway and is not required for Cdc14p release from the nucleolus (Fig.…”
Section: E S B I O S C I E N C E D O N O T D I S T R I B U T Ementioning
confidence: 99%
“…During interphase and early mitosis, a nucleolar protein Net1/Cfi1 binds to and sequesters Cdc14 in the nucleolus before being released into the nucleus and the cytoplasm (Visintin et al, 1999;Shou et al, 2001). Close examination of Cdc14 localization during cell cycle progression revealed that Cdc14 is released from the nucleolus in a biphasic manner (Stegmeier et al, 2002): a small fraction of Cdc14 release in early anaphase (FEAR) followed by a bulk of Cdc14 release in the late anaphase/telophase (MEN).…”
Section: Fear and Mitotic Exitmentioning
confidence: 99%
“…Hu et al (2001) demonstrated that Cdc5 directly phosphorylates and reduces the ability of Bfa1/Bub2 GAP to interact with Tem1, a step that facilitates the interaction between the GTP-loaded Tem1 and its downstream effector Cdc15 (Ro et al, 2002). The Cdc15-Dbf2/Mob1 protein kinase cascade then triggers the release of a bulk of Cdc14 from its nucleolus anchor Net1/Cfi1 (Visintin et al, 1999;Shou et al, 2001) (Figure 5). The MENreleased Cdc14 then dephosphorylates and activates APC/Cdh1 (Schwab et al, 1997;Visintin et al, 1997), stabilizes a Cdk1 inhibitor Sic1 (Mendenhall, 1993;Schwob et al, 1994), and promotes the nuclear entry of an SIC1 transcription factor Swi5 (Knapp et al, 1996;Toyn et al, 1996).…”
Section: Fear and Mitotic Exitmentioning
confidence: 99%